Development Graphic Organizers as Web-Based Learning in Writing an Opinion Essay - Lambe, Livianni; Degeng, I Nyoman Sudana; Cahyono, Bambang Yudi; Praherdhiono, Henry (Edutechnium Journal of Educational Technology, 2024)
The study aims to describe the development process of readymade Graphic organizers applied in Web-Based Learning (WBL) to increase students writing ability of opinion essays. The method was R and D using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). To obtain the data, the researcher used a questionnaire using a 5-point Likert Scale. The questionnaires were distributed to experts and users and the result divulged the overall average 4.616 (4.62) categorized perfectly. The product was able to work well whereas the readymade graphic organizers assisted learners to write their opinion essays cohesively and coherently. The learning materials in this WBL use Youtube to help students learn about elements of writing and language individually and independently. When developing this product in web-based learning, it cognized ethical dimension, institution, management, technology, pedagogy, interface system, source, and evaluation. The graphic organizer applied on web-based learning endowed positive values to lectures and scholars.